Sm-Nn AND U-Pb AGE OF METABASIC DIKES IN THE GRANULITE-GNEISS DOMAIN OF THE ALDAN SHIELD AS EVIDENCE OF PALEOPROTEROZOIC THERMOTECTOGENESIS DURATION - Glukhovskii M.Z.; Kuz'min M.I.; Bayanova T.B.; Serov P.A. (My University, 2007)
The integral process of autonomous deformation, magmatism, and metamorphism superimposed on seemingly consolidated older rock complexes was called thermotectogenesis by Pavlovskii. The most vigorous tectonothermal events that affected the Archean tectonic units of the Earth’s crust occurred in the Paleoproterozoic 2.76–1.65 Ga ago as a manifestation of mantle plumes. As elsewhere, the Paleoproterozoic thermotectogenesis was widespread in the Aldan Shield and resulted in the formation of its zonal structure, including the central granulite–gneiss domain and granite–greenstone framework; the emplacement of autonomous anorthosite massifs and complementary granitoids; and the injection of mafic dikes, which are regarded as indicators of mantle plumes. These processes were accompanied by rearrangement of isotopic systems, so that the dating of rocks encounters problems. This work is aimed at estimation of the duration of the aforementioned processes on the basis of geological and isotopic data on mafic dikes in the Sunnagin enderbite dome that occupies the northern sector of the multidomal granulite–gneiss domain of the Aldan Shield
Keywords: Paleoproterozoic; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская